Transivitas dalam Bahasa Indonesia dan Bahasa Sunda - Puspa Mirani Kadir; Pika Yestia Ginanjar; Cece Sobarna (Badan Pengembangan dan Pembinaan Bahasa, 2021)
The phenomenon of language is found mainly in Indonesian language and Sundanese language, one of which is the passive verbs; especially when the verb experiences the process of forming derivative words, either through affixation, reduplication, and compounding. Hopper and Thomson (1980) explain the relationship of transitivity and diathesis in the grammatical structure of verbs, especially in the field of study of affectedness of object; transitivity is divided into two types; (1) structural transitivity related to the predicate and two main arguments; and (2) traditional transitivity related to all elements in a clause transferring the action from agent to patient. This research aims to describe the transitivity level of Indonesian language by doing contrastive research with Sundanese language, based in the theory of Hopper and Thompson (1980) which focuses on the middle construction. The Sundanese language data is taken from sample sentences in Mangle Magazine (Edition 2018-2019), the drama script